Behaviour of sexually deceived ichneumonid wasps and its implications for pollination in Cryptostylis (Orchidaceae) - Weinstein, A.; Davis, B.; Menz, M.; Dixon, Kingsley; Phillips, R. (Wiley-Blackwell, 2016)
Pollination via sexual deception is hypothesised to be associated with more frequent outcrossing and greater pollen dispersal distances than strategies involving food-foraging behaviour. In this study, we investigated the behaviour and movement distances of Lissopimpla excelsa (Hymenoptera: Ichneumonidae), and their implications for the pollination of the sexually deceptive Cryptostylis ovata (Orchidaceae). Pollinator observations revealed that while L. excelsa will alight on multiple flowers within a single visit to a patch of orchids, the frequency of attempted copulation decreases with successive visits, suggesting that pollinator learning may inhibit within-patch pollen transfer. Mark-recapture demonstrated that 25% of wasps revisited inflorescences within a day and 50% revisited within a week. Despite the apparent site fidelity of some individuals, L. excelsa often move over large distances (maximum = 625 m), and are capable of dispersing pollen between patches. To resolve the consequences of pollination by sexual deception of ichneumonids, we compared our results with those from studies of other sexually deceptive systems. While pollination rates were comparable with other sexually deceptive orchids, L. excelsa showed high rates of column contact and moved over large distances relative to other sexually deceived pollinators. Among sexually deceptive orchids in general, the frequency of column contact was not correlated either with the frequency of pseudocopulation or with pollination rate. These results suggest that the consequences of pollination by sexual deception may vary extensively between plant taxa due to variation in floral traits, and behavioural differences between pollinator groups.